The establishment of safety practices conceptual framework for collapse accident in improving the construction site management: a case study for building & infrastructure works in Pulau Pinang / Muhammad Syahir Yusof@Abdullah - Yusof@Abdullah, Muhammad Syahir (2018)
Currently in Malaysia, cases of construction site accidents increase rapidly. This is due to building and infrastructure of construction work are exposed to too many risks and collapse accidents that contributed to many severe and fatal injuries every year. Thus, the objectives of this research are to determine the main causes of collapse accident, to investigate the main attributes of safety practice as a prevention tool for collapse accidents and to establish the safety practices conceptual framework for collapse accident in improving the construction site management. The data were collected through questionnaires survey from 30 respondents and analysed using SPSS Software version 23.0 using ranking analysis based on mean and standard deviation value. Besides, direct observation method was used and the data were analysed using frequency analysis. Then, the results found that majority of the total respondents agreed that the most critical main causes of collapse accidents are collapse accidents are management, unique nature of the industry, human element and unsafe method. Besides, the safety practices attributes were matched with suitable main causes by followed the result from synthesised of literature review. From the survey result, it was found that, there are four (4) priority safety practice attributes for every causes of collapse accident. Finally, all the findings will be used to develop a safety practices conceptual framework for collapse accidents at construction sites as a guideline to construction practitioners especially for the contractors to monitor and take action in the future construction activities to reduce collapse accidents in generally as one of the imposed safety at the construction sites especially in the building and infrastructure works.